Integration of wearable sensors into the evaluation of running economy and foot mechanics in elite runners - Muniz-Pardos, B.; Sutehall, S.; Gellaerts, J.; Falbriard, M.; Mariani, B.; Bosch, A.; Asrat, M.; Schaible, J.; Pitsiladis, Y. P. (Current Sports Medicine Reports, 2018)
Running economy, known as the steady-state oxygen consumption at a given submaximal intensity, has been proposed as one of the key factors differentiating East African runners from other running communities around the world. Kenyan runners have dominated middle- and long-distance running events and this phenomenon has been attributed, in part at least, to their exceptional running economy. Despite such speculation, there are no data on running mechanics during real-life situations such as during training or competition. The use of innovative wearable devices together with real-time analysis of data will represent a paradigm shift in the study of running biomechanics and could potentially help explain the outstanding performances of certain athletes. For example, the integration of foot worn inertial sensors into the training and racing of athletes will enable coaches and researchers to investigate foot mechanics ( e.g., an accurate set of variables such as pitch and eversion angles, cadence, symmetry, contact and flight times or swing times) during real-life activities and facilitate feedback in real-time. The same technological approach also can be used to help the athlete, coach, sports physician, and sport scientist make better informed decisions in terms of performance and efficacy of interventions, treatments or injury prevention; a kind of "telesport" equivalent to "telemedicine." There also is the opportunity to use this real-time technology to advance broadcasting of sporting events with the transmission of real-time performance metrics and in doing so enhance the level of entertainment, interest, and engagement of enthusiasts in the broadcast and the sport. Such technological advances that are able to unobtrusively augment personal experience and interaction, represent an unprecedented opportunity to transform the world of sport for participants, spectators, and all relevant stakeholders.